The Role Of International Technical Cooperation Between Universities In The Tranfer Of Techbology With Special Reference To Agriculture - Tejoyuwono Notohadiprawiro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1984)
-